Occupational Therapy’s Unique Contribution to Chronic Pain Management: A Scoping Review - Émilie Lagueux; Andréa Dépelteau; Julie Masse (Pain Research and Management)
Occupational therapy (OT) makes a unique contribution to chronic pain (CP) management due to its overarching focus on occupation. The aim of this scoping review was to describe current knowledge about this contribution by documenting OT roles, models, assessments, and intervention methods used with adults living with CP. A systematic search exploring 10 databases and gray literature from 2006 to 2017 was conducted. Fifty-two sources were retained and analysed. Results bring forward the main role of OT being improving activities and participation (76.9 %), the Canadian Model of Occupational Performance (9.6 %), and the Canadian Occupational Performance Measure (21.2 %). Within the 30 reported interventions, 73.3% related directly to the person, 20% pertained to occupation (activities and participation), and 6.7% addressed environmental factors. The distinction and complementarity between the bottom-up and the top-down approaches to OT intervention were discussed. This review highlights OT specificity in adult CP management.